Sir2 deletion prevents lifespan extension in 32 long-lived mutants - Delaney, Joe R. (2011)
Activation of Sir2-orthologs is proposed to increase lifespan downstream of dietary restriction (DR). Here we describe an examination of the effect of 32 different lifespan-extending mutations and four methods of dietary restriction on replicative lifespan (RLS) in the short-lived sir2Δ yeast strain. In every case, deletion of SIR2 prevented RLS extension; however, RLS extension was restored when both SIR2 and FOB1 were deleted in several cases, demonstrating that SIR2 is not directly required for RLS extension. These findings indicate that suppression of the sir2Δ lifespan defect is a rare phenotype among longevity interventions and suggest that sir2Δ cells senesce rapidly by a mechanism distinct from that of wild-type cells. They also demonstrate that failure to observe life span extension in a short-lived background, such as cells or animals lacking sirtuins, should be interpreted with caution.